17th International Conference on Biomagnetism Advances in Biomagnetism - Biomag 2010 - March 28 - April 1, 2010 Biomag March 28 - April 1, 2010 - Supek, Selma; Sušac, Ana (IFMBE Proceedings,, 2010)
This Volume presents the proceedings of the 17th International Conference on Biomagnetism to be held in Dubrovnik, Croatia from Sunday, March 28 through Thursday, April 1, 2010. It presents latest developments in instrumentation, modeling approaches, basic and clinical biomedical studies of Biomagnetism The interdisciplinary field of biomagnetism includes dynamic and evolving SQUID-based technologies offering advanced real-time methods for noninvasive assessments of magnetic signals from the brain, heart and other organs as well as a range of modeling, mathematical and computational methods for functional source localization approaches. Excellent spatial resolution and unique, millisecond, temporal resolution of biomagnetic techniques allow insights into cortical neurodynamics and neurobiological basis of the human brain and heart functions in health and disease.